Orang Tua dan Sekolah dalam Pembentukan Karakter Anak Usia Dini - Wisman, Yossita; Daniel, Susan; Bernisa, Bernisa (FKIP Universitas Palangka Raya, 2025)
This research originates from issues found in the field regarding the crucial role of parents and schools in shaping the character of early childhood. TK PGRI Samba Bakumpai, Central Kalimantan, implements various programs, activities, and habits that support the character development of its students. Character reflects a person's traits, habits, or personality, which are formed through the internalization and application of certain values, serving as the foundation for thinking, behaving, and acting. This study employs a descriptive narrative method to present data in detail through a scientific narrative. Data collection was conducted through observation and documentation, followed by data reduction, data presentation, and conclusion drawing. The research findings indicate that the efforts made by TK PGRI Samba Bakumpai RT 8, Katingan Tengah Regency, Central Kalimantan, in shaping students' character can be considered successful. The school fosters various character values, such as compassion, mutual respect, sharing, leadership, faith, discipline, and responsibility.